Rancang Bangun Sistem Informasi Pemesanan Jasa Kompon Mobil Berbasis Web Menggunakan Metode Waterfall (Studi Kasus: Kompon Mobil Gendrux Kartasura) - Stevanus Handriyanto; Handoko Handoko (Subaltern Inti Media, 2026)
The development of information technology has provided convenience in various fields, including vehicle repair services. One highly demanded service is mobile car polishing (kompon) to restore scratched or lightly damaged vehicle body surfaces. However, conventional booking processes often lead to scheduling conflicts, data recording errors, and a lack of accurate service status transparency. This study aims to design and develop a web-based car polishing service booking system. The primary advantage and innovation of this system, which differentiates it from previous studies, is the integration of a real-time scheduling algorithm that automatically prevents double-booking and features specific status tracking tailored for on-demand service models. The system was developed using the Waterfall SDLC (Software Development Life Cycle) method, with data collection conducted through observation, interviews, and literature studies. The application was built using the PHP programming language and a MySQL database. System evaluation was carried out using Blackbox Testing to ensure all functionalities operate without logical errors, and User Acceptance Testing (UAT) to measure end-user satisfaction. The results indicate that the developed system effectively facilitates online bookings, prevents scheduling overlaps, and assists service providers in structured order management. Furthermore, the testing confirms that all features function flawlessly, and the application has achieved a high level of user acceptance.